Design and development of extraction and filtering system for misai kucing tea in frutania company - Chong, Ying Xian (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The purpose of this project is to design and develop an extraction and filtering system for Misai Kucing tea in Frutania Company. Extraction and filtering process is one of the major process for product Misai Kucing tea where currently using a manual system to extract and filter the tea leaves in Frutania Company. Extraction and filtering system is developed to increase the productivity rate and reduce manpower for Misai Kucing tea processing.